Soccer anatomy - Kirkendall, Donald T., ....- (Champaign : Human Kinetics, 2011)
"Soccer Anatomy" combines step-by-step instructions and full-color anatomical illustrations to convey proper form of the 79 soccer-specific exercises that increase speed, strength, and agility as well as prevent injury. Exercises are arranged anatomically, making it easy to target specific muscle groups.
Your illustrated guide for soccer strength, speed, and agility
Keywords: Voetbal